An approach to heterodiarylmethanes via sp2–sp3 Suzuki−Miyaura cross-coupling. Issue 26 (30th June 2016) - Stewart, Gavin W.; Maligres, Peter E.; Baxter, Carl A.; Junker, Ellyn M.; Krska, Shane W.; Scott, Jeremy P.
Abstract: The synthesis of a range of structurally diverse diarylmethanes via the Suzuki−Miyaura cross-coupling of aryl methane acetates and arylboronic acids is reported, including several challenging examples containing nitrogen, oxygen and sulfur heteroatoms in one or both coupling partners. A single set of optimized conditions was used to generate the diarylmethanes in 52–91% yield. Graphical abstract: